2008
DOI: 10.1007/s11999-007-0091-5
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Reverse Endoprosthesis to Glenohumeral Kinematics

Abstract: After placement of a reverse shoulder endoprosthesis, range of motion is usually still compromised. To what extent this occurs from limitation in motion of the reverse endoprosthesis is, however, unclear. We measured the motion pattern of 16 patients (18 shoulders) during three active and passive range of motion tasks using a six degree-of-freedom electromagnetic tracking device. Despite rotator cuff deficiencies, glenohumeral elevation contributed roughly two-thirds of the total thoracohumeral elevation, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…It is not completely clear if this difference is only caused by the type of prosthesis, or also by the (isokinetic) force generating capacity or a combination of both. Previous research (Bergmann et al, 2008) suggested that the limited glenohumeral motion of the RSA seems to be the result of a lack of joint torque generation, with moderate correlations between post-operative clinical outcome scores (Constant-Murley, DASH and SST) and the abduction and external rotation torques (Alta et al, 2012). Therefore, the evaluation of isokinetic shoulder strength after RSA in comparison to TSA patients may be of interest in modeling dynamic upper extremity function and may supply more specific information on the influence of the type of prosthesis on the force generating capacity, particularly where comparative data are only limited available (Puskas et al, 2013) for those two clinical scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not completely clear if this difference is only caused by the type of prosthesis, or also by the (isokinetic) force generating capacity or a combination of both. Previous research (Bergmann et al, 2008) suggested that the limited glenohumeral motion of the RSA seems to be the result of a lack of joint torque generation, with moderate correlations between post-operative clinical outcome scores (Constant-Murley, DASH and SST) and the abduction and external rotation torques (Alta et al, 2012). Therefore, the evaluation of isokinetic shoulder strength after RSA in comparison to TSA patients may be of interest in modeling dynamic upper extremity function and may supply more specific information on the influence of the type of prosthesis on the force generating capacity, particularly where comparative data are only limited available (Puskas et al, 2013) for those two clinical scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Bergmann et al (2008) previously described a better passive than active RoM in patients with a RSA and presumed that the limited glenohumeral motion resulted from a lack of joint torque generation rather than a structural limitation caused by the prosthetic design. We recently demonstrated a correlation between the postoperative Constant-Murley score and the abduction and external rotation torques in RSA patients (Alta et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The Ovoide prosthesis was the first step toward a ''nonanatomic'' solution for medializing the COR, but the application of medialization of the rotation center combined with the ''reverse'' design supported in the 1970s represents the deep thoughts of Grammont's principles. Several studies have shown medialization of the rotation center substantially increases the deltoid lever arm with the ability to restore glenohumeral mobility in elevation when a rotator cuff tear is absent [8,13,26]. Moreover, the power exerted by the deltoid muscle is increased by the restoration of muscle tension due to the lowering of the humerus [11].…”
Section: Discussionmentioning
confidence: 99%
“…Since the scapulae were fixed on steel plates and mounted on the testing tower, scapulothoracic motion was eliminated. Clinical studies have shown that glenohumeral motion contributes on average two thirds to the entire thoracohumeral ROM in reverse shoulder arthroplasty [1]. Since scapulothoracic motion was eliminated, the measured movements represent the passive ROM of the prosthetic articulation, not physiological ROM of a patient.…”
Section: Discussionmentioning
confidence: 99%